Effects of huoxin formula on the arterial functions of patients with coronary heart disease - Yan Xu; Hongyi Hu; Yi Li; Rong Cen; Chengzeng Yao; Wenhuan Ma; Minhua Huang; Yahui Yin; Hongzhi Gao; Yongming Liu; Alexander Endler (Taylor & Francis Group, 2019)
Context: Huoxin formula is a Traditional Chinese Medicine for coronary heart disease (CHD) treatment. Objective: To explore the therapeutic mechanism of the Huoxin formula on arterial functions in CHD patients. Materials and methods: Fifty-eight CHD patients receiving cardiovascular drugs including β-receptor blocker, statins, and antiplatelet medications or others were randomized into intervention [additionally 13.5 g Huoxin formula granules dissolved in 150 mL warm water per time, twice a day (n = 30)] and control [only cardiovascular drugs (n = 28)] groups. Serum biomarkers (hs-CRP, IL-18, IL-17, TNF-α, MMP-9), and cardiovascular indicators of the common and internal carotid arteries (ICAs) were monitored before and after the treatments. Results: After 3 months of treatment, the increases of intima-media thicknesses (IMT) of the left and right common carotid arteries (CCAs) as well as of the left and right ICAs and the increases of the left and right cardio-ankle vascular index were all significantly (all p < 0.001) less in the intervention than in control group (all p < 0.001). Serum concentrations reductions of hs-CRP, IL-18, IL-17 and MMP9 (all p < 0.001) levels were higher in the intervention compared to the control group, which correlated with the changes of left ICA (hs-CRP: r = 0.581, p = 0.009; IL-18: r = 0.594, p = 0.007; IL-17: r = 0.575, p = 0.006). Discussion and conclusion: Since the Huoxin formula improved arterial functions and reduced inflammatory factor activities in CHD patients, a large-scale clinical trial is warranted.